2019
DOI: 10.1016/j.ophtha.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Determining Subclinical Edema in Fuchs Endothelial Corneal Dystrophy: Revised Classification using Scheimpflug Tomography for Preoperative Assessment

Abstract: Subclinical corneal edema in FECD can be detected by Scheimpflug tomography. We recommend classifying FECD corneas as having clinically definite edema (based on slit-lamp examination), subclinical edema (based on tomographic features without clinically definite edema), or no edema (no tomographic or slit-lamp features of edema). This classification is independent of CCT and should be considered when evaluating FECD eyes for cataract surgery or EK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
138
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(145 citation statements)
references
References 25 publications
2
138
1
4
Order By: Relevance
“…Recently, we described a Scheimpflug imaging classification of FECD that categorizes the disease into having clinically obvious edema (edema visible by slit-lamp examination with thickening of the stroma, Descemet or deep stromal folds, stromal clouding determined by sclerotic scatter, microcystic epithelial edema or bedewing, or subepithelial bullae), subclinical corneal edema (based on the presence of specific tomographic features; see below), or no edema (absence of the specific tomographic features of edema), independent of CCT. 1 We found that 3 tomographic pachymetry map and posterior elevation map patternsdspecifically the presence of irregular isopachs, displacement of the thinnest point of the cornea, and focal posterior surface depressiondwere present in FECD with subclinical corneal edema. The classification recommended that the diagnosis of FECD be made clinically with slit-lamp biomicroscopy and categorized further by using Scheimpflug tomography when corneal edema was not clinically obvious.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Recently, we described a Scheimpflug imaging classification of FECD that categorizes the disease into having clinically obvious edema (edema visible by slit-lamp examination with thickening of the stroma, Descemet or deep stromal folds, stromal clouding determined by sclerotic scatter, microcystic epithelial edema or bedewing, or subepithelial bullae), subclinical corneal edema (based on the presence of specific tomographic features; see below), or no edema (absence of the specific tomographic features of edema), independent of CCT. 1 We found that 3 tomographic pachymetry map and posterior elevation map patternsdspecifically the presence of irregular isopachs, displacement of the thinnest point of the cornea, and focal posterior surface depressiondwere present in FECD with subclinical corneal edema. The classification recommended that the diagnosis of FECD be made clinically with slit-lamp biomicroscopy and categorized further by using Scheimpflug tomography when corneal edema was not clinically obvious.…”
mentioning
confidence: 63%
“…Methods have been proposed for determining whether to perform cataract surgery alone or in combination with keratoplasty in the setting of FECD, including assessing absolute central corneal thickness (CCT) 4,5 and endothelial cell density, 6 but these measurements are misleading for clinical decision making. 1,7 An increase in CCT over time can indicate disease progression but needs to be considered in the context of corneal thickness before disease onset. A cutoff of corneal backscatter measured by confocal microscopy has also been suggested to help with surgical decision making, 5 although this method is difficult to perform in clinical practice.…”
mentioning
confidence: 99%
“…All of these features were present in every case with clinically definite edema (n ¼ 15) and 13 (81.25%) of 16 FECD cases with suspicious edema. 2 However, at least 1 of such features was present in 5 (6.8%) of 74 control eyes with no guttae and 26 (42%) of the 62 FECD cases with no edema. 2 The "false-positive" control cases indicate these tomographic characteristics could occur in other clinical conditions related to irregular astigmatism without guttae.…”
mentioning
confidence: 91%
“…2 However, at least 1 of such features was present in 5 (6.8%) of 74 control eyes with no guttae and 26 (42%) of the 62 FECD cases with no edema. 2 The "false-positive" control cases indicate these tomographic characteristics could occur in other clinical conditions related to irregular astigmatism without guttae. However, their presence in the FECD cases considered not to have edema deserves longitudinal analysis because those eyes could represent the "true" subclinical cases that are not detectable by biomicroscopy.…”
mentioning
confidence: 91%
See 1 more Smart Citation